Studi Literatur : Artificial Inteligence Dalam Dunia Perpajakan Di Indonesia - Pramesti, Retta Farah; Emalia, Deasy (Yayasan Cita Cendikiawan Al Kharizmi, 2024)
This study aims to examine how the role of AI in the tax system in Indonesia, the challenges and benefits of tax AI and Tax AI seen from the renewal of the Core Tax Administration System (PSIAP) or Core Tax Administration System (CTAS) as the future in the world of taxation. This research is of qualitative type. The population in this study were 10 journals selected based on literature review materials, read and then analyzed. The results showed that AI has great potential in improving efficiency, accuracy and transparency in the tax system in Indonesia. The application of AI technology in taxation in Indonesia can speed up the administrative process, simplify tax reporting and payment and increase compliance for taxpayers in paying taxes. The application of AI in taxation tends to support the digitization of the tax system through initiatives such as the Core Tax Administration System (CTAS) Update so that in the future it can be more responsive and adaptive in the development of government policies in Indonesia. This analysis is based on theoretical and technical aspects without in-depth exploration of the social and economic impacts of AI implementation in taxation in Indonesia.